Kauniit joulun muistot - Mäkelä, Miia; Karjalainen, Alpo-Ville; Karjalainen, Alpo-Ville; Pentti, K. ([Kustannuspaikka tuntematon] : [kustantaja tuntematon], 2000)
1 kappale.
Miia Mäkelä (lauluääni).
Keywords: joululaulut